Julie Taymor’s Ideographs in Her Adaptations of Shakespeare’s Titus Andronicus and The Tempest - Stakor, Kristijan (Anafora, 2023)
The aim of this paper is to show the unique visual style in director Julie Taymor’s vividly filmed adaptations of Shakespeare’s plays, The Tempest and Titus Andronicus by concentrating on the visual elements called ideographs or ideograms. By definition, these ideographs are usually symbols that represent a particular idea or a thing rather than a word. I will argue that ideographs are also present in her films, Titus (1999) and The Tempest (2010), and that Taymor’s vast theatrical knowledge adds layers of meanings into filmed sequences. Shakespeare’s plays, burdened with foul deeds of war, revenge, struggle, and witchcraft almost invite the director not to settle with the ordinary, but to use contrasting colors and costumes from opposing eras, letting her show us his world through her own prism. Therefore, these adaptations are exceptional not only because of Taymor’s untypical use of familiar historical elements in production design but also because of her use of nonlinguistic devices in order to both express admiration for and criticize the situations presented in the original text. The paper also argues that Taymor’s films should be viewed as cross-cultural and intercultural adaptations, rather than American adaptations, because she uses Eastern theatrical elements and European heritage in order to underline the complexity and extravagant nature of events depicted in the plays.